Kepuasan dan Loyalitas Konsumen Restoran Bakso Bakwan Malang (Jurnal Agribisnis Indonesia, 2023)
Bakso is the popular food in Indonesia and has many kinds of variation. One of them is Bakso Bakwan Malang Cak Su Kumis which has been established for decades by maintaining its unique taste. This study aims to identify the characteristics, analyze the level of satisfaction and the consumer loyalty. In this study, there were 100 respondents included. The methods used in this study are descriptive analysis, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA) and brand loyalty pyramid analysis. The results of the CSI analysis showed that the value of customer satisfaction has a score of 79,99 which states that consumers are satisfied. Besides that, analysis of the level of consumer loyalty shows that even though consumers are satisfied with the restaurant performance, consumers are not loyal yet. Hence, the performance improvement can be conducted by improving attributes with low performance such as sale promotion, serving time, name board, price and food hygiene.